The New York times parent's guide to the best books for children - Lipson, Eden Ross (New York Three Rivers Press, 2000)
Provides reviews of more than one thousand classic children's books, ranging from picture books and early readers to young adult titles, along with more than fifty subject indexes and bibliographical listings of authors and illustrators.
"Originally published in different form by Times Book in 1988 and 1991."--title page verso.
Includes bibliographical references (page 519) and indexes.
Keywords: Children's literature -- Bibliography; Reading -- Parent participation; Children -- Books and reading